Mobile learning : a handbook for developers, educators, and learners - McQuiggan, Scott; Kosturko, Lucy.; McQuiggan, Jaime; Sabourin, Jennifer; Ohio Library and Information Network (Hoboken, New Jersey : Wiley, 2015)
"Explore the game-changing technology that allows mobile learningto effectively reach K-12 students Mobile Learning: A Handbook for Developers, Educators andLearners provides research-based foundations for developing, evaluating, and integrating effective mobile learning pedagogy. Twenty-first century students require twenty-first centurytechnology, and mobile devices provide new and effective ways toeducate children. But with new technologies come new challenges--therefore, this handbook presents a comprehensive look at mobile learning bysynthesizing relevant theories and drawing practical conclusionsfor developers, educators, and students. Mobile devices--in ways that the laptop, the personalcomputer, and netbook computers have not--present theopportunity to make learning more engaging, interactive, andavailable in both traditional classroom settings and informallearning environments. From theory to practice, MobileLearning explores how mobile devices are different than theirtechnological predecessors, makes the case for developers, teachers, and parents to invest in the technology, and illustratesthe many ways in which it is innovative, exciting, and effective ineducating K-12 students. Explores how mobile devices can support the needs ofstudents Provides examples, screenshots, graphics, and visualizations toenhance the material presented in the book Provides developers with the background necessary to create theapps their audience requires Presents the case for mobile learning in and out of classroomsas early as preschool Discusses how mobile learning enables better educationalopportunities for the visually impaired, students with Autism, andadult learners. If you're a school administrator, teacher, app developer, orparent, this topical book provides a theoretical, well-researcheddiscussion of the pedagogical theory and mobile learning, as wellas practical advice in setting up a mobile learning strategy"--
Includes bibliographical references and index
Keywords: Educational technology; Mobile communication systems in education; Electronic books